A Computational Bibliometric Analysis of Esport Management using VOSviewer - Ginting, Selvia Lorena Br (Universitas Komputer Indonesia, 2023)
The project aims to combine visualization study with VOSviewer and Publish or Perish software to conduct a computerized bibliometric analysis of the phrase